RESPONS BEBERAPA VARIETAS BAWANG MERAH AKIBAT PERBEDAAN JARAK TANAM DALAM SISTEM TUMPANGSARI PADA LAHAN BEKAS TSUNAMI - Jumini Jumini; Ainun Marliah; Rais Fahmi (Jurnal Floratek, 2011)
This study was aimed at examining the growth and yield of onion due to different spacing of red chili in intercropping system on the tsunami affected land. This research used a randomized block design of 4 x 2 with 3 replications. Factors studied were (1) red onion varieties, consisting of 4 levels: Juna Bima, Bima Curut, Warso and Kuning Tablet (2) spacing, consisting of 2 levels: 50 cm x 60 cm and 50 cm x 70 cm. Results showed that onion varieties in intercropping system with red chili exerted highly significant effects on plant height of red onion at age of 30 days after planting (DAP) and number of tillers at  age of 15 and 45 DAP, as well as on wet and dry weight of tuber, and exerted significant effects on plant height at 15 and 45 DAP, and number of tillers at age of 30 DAP. The best onion variety was Kuning Tablet.  Spacing distance of chili in intercropping system with red onion exerted highly significant effects on plant height of red chili at age 30 DAP, and a significant effect on plant height at 45 DAP and no significant effect on plant height and number of productive branches at age 60 DAP.